ENHANCING WRITING POWER THROUGH LEADING QUESTIONS STRATEGY - Hima Nurul Hidayah; Sri Wahyuni (Universitas islam Negeri Alauddin Makassar, 2022)
Writing is difficult skill in English. This study aims to determine the improvement of students’ writing skills using a leading question strategy. The study was conducted at the bilingual Madrasah Aliyyah class in Kediri. In fact, in the preliminary study, the researcher found that students had difficulty in writing recount texts. Students cannot retell past experiences because of lack of vocabulary and had no ideas for writing. The researcher used leading questions strategy to help students improve their writing skill in recount text. The researcher applied the classroom action research design by collecting data through observation checklists and tests. The research is considered successful if more than 80% of the students of the class achieve a score greater than or equal to 80 in the students' writing test. The finding of this study shows that there is improvement of students’ writing skill in recount text after implementing leading question strategy in one cycle with four meetings. The success percentage of this technique is 94 %, and the average score is 88. The average student scores 88. This means that almost all students pass the written test. The attitude of the students during the writing process was very good. Students' enthusiasm in writing recount text increased significantly. From the results of all meetings, it can be concluded that the use of leading questions strategy can improve students’ writing skill in recount text.